Distribution of carbon emissions in the UK : implications for domestic energy policy - Preston, I; White, V; Thumim, J; Bridgeman, T; Brand, C (Joseph Rowntree Foundation, 2013)
The report looks at the distribution of carbon emissions and abatement opportunities of households in England, and the implications for energy and climate change policy impacts. The UK government has a target to reduce greenhouse gas emissions by 80% on 1990 levels by 2050. In addition there are statutory targets to ensure that no household is in fuel poverty by 2016. An understanding of how current and proposed policy approaches to meeting these targets are likely to impact differentially on domestic energy consumers is fundamental to ensuring policies are both fair and effective. This research project uses advanced modelling techniques to develop and analyse the datasets needed to support and further understanding of: • the distribution of carbon emissions – from energy consumed in the home and through personal travel by car, public transport and aviation – across households in Great Britain; • the impact of existing government energy and climate policies on consumer energy bills and household emissions in England; • the potential for an alternative approach to reducing emissions in the domestic sector through a wide-scale retrofit of the housing stock.